Variations in antimalarial components of Artemisia annua Linn from three regions of Uganda. - Engeu, Patrick Ogwang; Omujal, Francis; Agwaya, Moses; Kyakulaga, Hassan; Obua, Celestino (African health sciences, 2015)
Introduction: Artemisia annua plant from the family Asteracea is a powerful antimalarial plant introduced to Uganda around 2003. In addition to the artemisinin component, the plant also contains flavonoids which work in synergy to artemisinin against malaria parasites. The plant also contains aromatic oils which repel mosquitoes. In this paper we report the variations in antimalarial components of A. annua samples from the regions cultivating it in Uganda. Methods: Artemisia annua samples were obtained from three regions that cultivated the plant at the time of this study. The samples were brought to laboratory, authenticated and processed. The levels of artemisinin, total flavonoids and aromatic components were quantified using high performance thin layer chromatography, ultra violet spectrophotometry and gas chromatography respectively. Results: Artemisinin and total flavonoids levels were higher in samples obtained from high land areas (western and south western region) compared to that obtained from lowland regions (central) i.e 0.8% Vs 0.4% and 2.6% Vs 1.5% respectively. The aromatic oils (mosquito repellent components) were similar with camphor component being highest and levels ranging from 75.4% to 79.0%. Conclusion: Our findings show that the active components in Artemisia annua cultivated and used in the Uganda vary with geographical regions and this calls for standardisation by source.
Keywords: Antimalarial components; Artemisia annua; Uganda; Variations